Analysis of The Legal Arguments in The Fatwa of The National Sharia Council of The Indonesian Ulema Council Number 22 Of 2002 Concerning Parallel Istishna - Komarudin, Parman; Rifqi, Muhammad; Yanova, Muhammad Hendri; Huda, Rahmatul (RSF Conference Series: Business, Management and Social Sciences, 2024)
This research aims to analyze the relevance and accuracy of the legal arguments in the National Sharia Council Fatwa No. 22/2002 on Parallel Istishna. With a qualitative research method and normative legal approach, the analysis in this study adapts the method used by Haisy (2019). The results show that the arguments of parallel istishna, which consist of hadith, fiqh rules, and aqliyah rules, are relevant to the content of the fatwa, especially in the fiqh rules section. However, to improve the accuracy and applicability of the evidence, it can be supplemented with other sharing evidence that is closer to the study of parallel istishna, including Surah Al-Kahf Verse 94, hadith related to the making of rings and pulpits, ijma' amaly, and istihsan. This research contributes to the study of parallel istishna, namely in terms of helping to identify and summarise the shar'i arguments as the legal basis for parallel istishna.